Spatiotemporal changes of ecosystem service trade-offs under the influence of forest conservation project in Northeast China - Jia, Guangliang; Dong, Yulin; Zhang, Siyu; He, Xingyuan; Zheng, Haifeng; Guo, Yujie; Shen, Guoqiang; Chen, Wei (Frontiers in Ecology and Evolution, 2022)
Trade-offs between ecosystem services are measures of the degree to which the changing differences between the individual ecosystem services. Although changes in ecosystem service trade-offs are critical for forest ecosystem management, spatiotemporal changes in trade-offs are currently less studied, especially under the influence of ecological engineering implementation. Therefore this study explored the spatiotemporal changes and drivers of ecosystem service trade-offs in various forest types following the implementation of the natural forest conservation project (NFCP), with the example of the Greater Khingan Mountains. Spatial analyses and root mean square error (RMSE) were applied to investigate spatiotemporal changes in trade-offs, and geodetector was employed to assess their driving factors. The results indicated that among all ecosystem service pairs from 1990 to 2020, the trade-offs between habitat quality and net primary productivity (NPP), NPP and soil conservation showed a growing trend. However, the trade-offs between habitat quality and water conservation, NPP and water conservation, and soil conservation and water conservation showed a declining trend. The ecosystem service trade-offs of coniferous (0.47) were higher than either broad-leaved (0.37) or shrubs (0.28). Moreover, changes in the ecosystem service trade-offs of all kinds of forests were spatially heterogeneous. The drivers with the greatest explanatory power in coniferous, broad-leaved, and shrubs were land use (22.68%), land use (15.19%), and NDVI (20.63%), respectively. Environmental factors contributed great mean explanatory power (62.27%–71.67%) to the trade-offs than anthropogenic activity factors. Therefore, spatiotemporal changes and drivers of trade-offs in different forests should be contemplated when conducting subsequent ecological restoration programs in the future.